Salvia fruticosa Induces Vasorelaxation In Rat Isolated Thoracic Aorta: Role of the PI3K/Akt/eNOS/NO/cGMP Signaling Pathway - M. Akhtar Anwar; Ali A. Samaha; Samar Ballan; Alaaeldin I. Saleh; Rabah Iratni; Ali H. Eid (Scientific Reports, 2017)
Abstract Salvia fruticosa (SF) Mill. is traditionally used for its antihypertensive actions. However, little is known about its pharmacologic and molecular mechanisms of action. Here we determined the effects of an ethanolic extract of SF leaves on rings of isolated thoracic aorta from Sprague-Dawley rats. Our results show that SF extract increased nitric oxide production and relaxed endothelium-intact rings in a dose-dependent (0.3 µg/ml–1 mg/ml) manner, and the maximum arterial relaxation (Rmax) was significantly reduced with endothelium denudation. Pretreatment of endothelium-intact rings with L-NAME (a non-selective inhibitor of nitric oxide synthase, 100 µM), or ODQ (an inhibitor of soluble guanylyl cyclase, 10 µM) significantly diminished SF-mediated vasorelaxation. Furthermore, SF induced Akt phosphorylation as well as increased cGMP levels in rings treated with increasing doses of SF. Prior exposure to PI3K inhibitors, wortmannin (0.1 µM) or LY294002 (10 µM), decreased cGMP accumulation and attenuated the SF-induced vasorelaxation by approximately 50% (Rmax). SF-evoked relaxation was not affected by indomethacin, verapamil, glibenclamide, tetraethylammonium, pyrilamine or atropine. Taken together, our results indicate that SF induces endothelium-dependent vasorelaxation through the PI3K/Akt/eNOS/NO/sGC/cGMP signaling pathway. Our data illustrate the health-orientated benefits of consuming SF which may act as an antihypertensive agent to reduce the burden of cardiovascular complications.